Application of Restitution for Criminal Acts Victims: Between Rules and Reality - Saputra, Trias; Mursyid, Ali Masyhar; Widyawati, Anis; Rahmiati, Rahmiati (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
Restitution is compensation provided to victims of a crime or their families by the perpetrator or a third party to cover losses from damage to property or income, suffering caused by the crime, and costs for medical or psychological care. Restitution serves as a critical mechanism for ensuring legal protection by aiding in the recovery of victims affected by criminal acts. This is regulated under Law Number 31 of 2014 on the Protection of Witnesses and Victims. However, challenges arise in its implementation, as seen in cases like Decision 1/PID.SUS/2023/PT Bdg, along with various issues in the application of restitution in court rulings, which will be analyzed in this study. This research examines these issues using normative legal research, employing both a legal and case study approach.